Estimating the breeding population size of the short-tailed shearwater using a nesting habitat suitability model - De Almeida E Silva, Nicolas; Monk, Jacquomo; Bustamante, Paco; Arnould, John P. Y. (Frontiers in Marine Science, 2025)
Population size estimates are important for conservation management. Conducting ground surveys is the most common approach used to provide population estimates but financial and logistical constraints often make this untenable for seabird species breeding on remote islands. The present study used previously collected count data of short-tailed shearwater burrows in conjunction with remote sensed environmental data to develop nesting habitat suitability models using Generalised Additive Models (GAMs). A global Generalised Additive Mixed Model (GAMM) including data from 14 islands around Wilsons Promontory (Bass Strait, Australia) revealed a preference of in short-tailed shearwaters for coastal grassland on a south-east terrain aspect with moderate incline to establish their breeding areas. The highest density areas were also away from the shoreline and with lower elevation. This global model, projected on 258 colonies representing the currently known breeding range of the species, predicted 11.26 (11.17–11.35) million burrows which, accounting for incomplete burrow occupancy, provided a total breeding population estimate of 12.84 (11.51–14.17) million individuals. While an increased spatial balance in training dataset could greatly improve the accuracy of global models, the estimate results of the present study are consistent with previous findings. This demonstrates the advantages of combining limited ground surveys data collection with such modelling approaches in comparison to more traditional ground survey extrapolations to produce species population estimates for burrowing seabirds.